HALY ‘ABBAS, Iranian Celebrated Physician who wrote an excellently organized Medical compendium - Pūyan, Naser (مجله اخلاق پزشکی - علمی پژوهشی, 2016)
One of the greatest physicians and encyclopedists in middle Ages in Europe was born in al-Ahwaz (c.930) from Old Persian stock. ‘Alī was moved to Shīrāz at an early age and made his medical studies under a physician of this city, Abū Mahir Mūsā ibn Sayyar. He practised medicine in Baghdad in mid – tenth century and served as physician to ‘Adud al-Dawla, to whom he dedicated his only composition, “Kāmil al- Sina‘a / Kitāb al- Malikī (The Complete Book of the Medical Art / The Royal Book). His principal work Kāmil al-Sinā ‘a was divided into two sections of theoretical and practical medicine, and each section contained 10 tracts on specialized topics. This compendium was deliberately written to fall midway between the lengthly al- Hāwī and brief al-Mansurī, the famous works of Rhazes. The Medieval Latin translators named the above mentioned magnum opus the “Liber Regius”. It covers the entire spectrum of Arabic (Islamic) medicine, including one chapter on diseases of the teeth. Haly ‘Abbas’ exact date of death is not known precisely, but according to some sources, he died between A.D.982 and 995.